Carbon supported lithium hydride nanoparticles: Impact of preparation conditions on particle size and hydrogen sorption. (23rd February 2017) - Bramwell, Peter L.; Ngene, Peter; de Jongh, Petra E.
Abstract: Nanosizing of light metal hydrides has yielded significant improvements to their hydrogen storage properties. We explored for the first time a procedure for preparing supported LiH nanoparticles. Impregnation of a carbon framework with a butyllithium solution, followed by reaction with gaseous hydrogen yielded LiH particles ranging in size from 2 nm to the micrometer scale. Reducing the reaction temperature from 300 °C to 100 °C, as well as the use of a t-butyllithium precursor instead of an n-butyllithium precursor, gave significant improvements on the degree of confinement of the LiH particles. The particle size of the LiH has a significant impact on the hydrogen release profile, 11 nm crystallites begin to release hydrogen as low as 100 °C under argon flow, a reduction of roughly 400 °C on the macrocrystalline system. The hydrogen release is reversible, with hydrogen uptake after desorption as high as 7.0 wt% w.r.t. LiH (0.8 wt% w.r.t the sample) under 0.1 bar of hydrogen at 200 °C and full uptake takes place within 5 min at 26 bar. This new preparation procedure for supported light metal hydrides is particularly relevant for the field of hydrogen storage. Graphical abstract: Highlights: A method for preparing a LiH/C nanocomposite has been developed. This was optimized by changing the precursor, temperature of reaction and carbon support. The optimized procedure consists of using a t-BuLi solution at 100 °C on a carbon xerogel support. This procedure yields H2 release at 100 °C with a reversible capacity of 7 wt% w.r.t. LiH.